2016
DOI: 10.17221/71/2015-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agricultural crops adjacent to forest on woody species browsing: Is it advantageous to have a tasty neighbour?

Abstract: ABSTRACT:Preference of biotopes and selection of food by wild herbivores are more complicated in a cultural landscape used for agriculture than in natural conditions. Agricultural management significantly affects the feeding as well as cover conditions of the environment and changes in quality and accessibility of food sources occur throughout the year. We studied the consumption of agricultural crops and impact on tree shoots by herbivores in a mosaic landscape. Large herbivores utilized the food supply on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Open habitats are often considered as providing forage of higher quality and quantity for large herbivores during the growing season (Kamler & Homolka 2016), but are often also perceived as riskier (Ciuti et al 2006; Grignoli et al 2007; Bjørneraas et al 2011). Previous studies demonstrated that the use of open habitat increases reproductive success in female roe deer (McLoughlin et al 2007; Bonnot et al 2018), although the strength of the response depends on predation pressure (Kjellander et al 2004) and personality (Monestier et al 2015; Bonnot et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Open habitats are often considered as providing forage of higher quality and quantity for large herbivores during the growing season (Kamler & Homolka 2016), but are often also perceived as riskier (Ciuti et al 2006; Grignoli et al 2007; Bjørneraas et al 2011). Previous studies demonstrated that the use of open habitat increases reproductive success in female roe deer (McLoughlin et al 2007; Bonnot et al 2018), although the strength of the response depends on predation pressure (Kjellander et al 2004) and personality (Monestier et al 2015; Bonnot et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Management of agroforestry resources is sometimes difficult in many rural areas due to the high presence of wild animals (Fratini et al, 2016), as their excessive presence can produce negative effects on agriculture or forest products (Innocenti et al 2015;Kamler and Homolka, 2016). Damage is caused on different kinds of crops, such as annual herbaceous crops or vineyards (Calenge et al, 2004;Bleier et al, 2016) or on forests, especially taking into account the difficulty of trees regeneration or growth (Gill and Beardall, 2001;Côté et al, 2004).…”
Section: Introductionmentioning
confidence: 99%